1990
DOI: 10.1073/pnas.87.7.2628
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid and cDNA sequences of a vascular endothelial cell mitogen that is homologous to platelet-derived growth factor.

Abstract: Glioma-derived vascular endothelial cell growth factor (GD-VEGF) is a 46-kDa dimeric glycoprotein mitogen with apparently greater specificity for vascular endothelial cells than the well-characterized fibroblast growth factors. The GD-VEGF cDNA sequence encodes a 190-amino acid residue subunit that is converted, by removal of an aminoterminal hydrophobic secretory leader sequence, to the mature 164-residue subunit characterized by direct amino acid sequencing. The GD-VEGF homodimeric subunit is homologous to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
152
0
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(158 citation statements)
references
References 29 publications
1
152
0
4
Order By: Relevance
“…In contrast to TGF-b, which mainly acts through monocyte chemotaxis (Wahl et al, 1987), VEGF is categorized as a direct angiogenic factor, as it stimulates endothelial cell proliferation and migration in the absence of any other cell type (PloueÈ t et al, 1989). Unlike FGF-1 or FGF-2 (Jaye et al, 1986;Abraham et al, 1986), VEGF is a secreted peptide with a typical NH 2 -terminal signal sequence (Leung et al, 1989;Keck et al, 1989;Conn et al, 1990b). The mitogenic activity of VEGF is mainly restricted to vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to TGF-b, which mainly acts through monocyte chemotaxis (Wahl et al, 1987), VEGF is categorized as a direct angiogenic factor, as it stimulates endothelial cell proliferation and migration in the absence of any other cell type (PloueÈ t et al, 1989). Unlike FGF-1 or FGF-2 (Jaye et al, 1986;Abraham et al, 1986), VEGF is a secreted peptide with a typical NH 2 -terminal signal sequence (Leung et al, 1989;Keck et al, 1989;Conn et al, 1990b). The mitogenic activity of VEGF is mainly restricted to vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 Vascular endothelial growth factor (VEGF) is a potent endothelial cell-specific cytokine that has been shown to have mitogenic and chemotactic effects on endothelial cells in vitro. 12 Wang et al showed that HIFa promotes angiogenesis and osteogenesis by elevating VEGF levels in osteoblasts. 13 In addition, VEGF has been shown to induce angiogenesis in many in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…Three classes of VPF clones that have been isolated from various cDNA libraries (Keck et al, 1989;Leung et al, 1989;Tischer et al, 1989;Conn et al, 1990a;Berse, unpublished data) contain three coding region variants. Tischer et al (1991) have shown that the human VPF/VEGF gene consists of eight exons and that the three VPF/VEGF mRNAs arise by alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, elicited macrophages were isolated from the peritoneal cavity 4-5 d after intraperitoneal injection of 20 ml sterile mineral oil (Hammond and Dvorak, 1972 (Keck et al, 1989;Leung et al, 1989). The guinea pig PCR product exhibits very high sequence homology (>90%) with human, as well as bovine and rat, VPF/VEGF cDNAs (Leung et al, 1989;Tischer et al, 1989;Conn et al, 1990a (5-50 ,ug) were size-fractionated on 1.2% agarose containing 6% formaldehyde and transferred to Nytran membranes (Schleicher and Schuell, Keene, NH). Hybridization was carried out for 24 h at 42°C in 50% formamide, 5X SSPE, 2.5X Denhardt's solution, 0.1% sodium dodecyl sulfate (SDS), and 10% dextran sulphate (Sambrook et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation